Impact of parallel projects management - Wani, Sharyar; Adam, Mutasim Elsadig; Abdullahi, Husein Osman; Ibrahim, Jamaludin (Centre for Promoting Ideas, USA, 2012)
The dramatic increase in the number of projects with the fact of increased stiffness in competition, the strength of enterprises faces a challenge to deliver the expected on time. Enterprises seem to be in dilemma regarding the implications of running simultaneous projects. Yet only a few have investigated the implications of parallel projects. The need of the industry is to formulate a model that will help them to face this challenge without really making changes to their structures. Therefore this paper aims to highlight the influence of parallel project management on project schedule, budget and product’s quality as well. To explore the implication, interviews were conducted among project managers from International Islamic University Malaysia (IIUM) who represented different work sectors. There seems to be a consensus that handling more than one project at a time is a challenge. The findings of this study show that most of project mangers suffer from the problem of change of focus from one project to another. As a result, some projects do not finish on time, lack quality standards, and need extra budget.